A Review on Cancer Dataset Classification using Data Mining Methods (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data analytics is observed as routine biomedical research domain focused on relevant clinical condition of cancer. Bioinformatics is characterized with consideration of several disease aspects. At present, several research focused on data processing of medical data. The medical data incorporates vast range of data such as miRNA, DNA with consideration of instances. The analysis of medical data expressed the micro array expression of gene with consideration of data attributes for minimal sample data count. For clinical and research process by using available data, medical data analysis extract equivalent data about genes. Data mining concentrated on analysis of cancer data with complexity analysis of underlying molecular diseases. The data mining of medical data is provided for processing reliable information and mechanism. However, construction of building model for medical data is complex for achieving reliable data. In this review, presented about contribution of data analysis for cancer data. The research concentrated on gene selection and data integration. Further, the analysis is based on the examination of data mining method analysis with consideration of gene data.